Characterization of Pleurotinae, with review of Pleurota species close to P. aristella (Linnaeus) from Morocco (Lepidoptera: Gelechioidea: Oecophoridae) - Kaila, Lauri; Mutanen, Marko; Sihvonen, Pasi; Tyllinen, Juha; Tabell, Jukka (Zootaxa, 2019)
Morphological traits characterizing and delimiting Pleurotinae (Oecophoridae) are provided and discussed. The evidence supports the validity of the subfamily as suggested by recent molecular studies. The Pleurota aristella (Linnaeus, 1767) species group is characterized, and six new species belonging to the group from Morocco are described: Pleurota tricolor Tabell, sp. nov., P. pellicolor Tabell, sp. nov., P. lacteella Tabell, sp. nov., P. moroccoensis Tabell, sp. nov., P. ochreopalpella Tabell, sp. nov., and P. atlasensis Tabell, sp. nov. Habitus images and label data are provided for the types of P. goundafella Zerny, 1935; P. insignella Zerny, 1935; P. ochreostrigella Baker, 1885; P. macrosella Rebel, 1900; P. staintoniella Baker, 1888; P. mauretanica Baker, 1888; and P. algeriella Baker, 1885. DNA barcodes of the new species are compared with all available Pleurotinae sequences (BIN n = 117) in BOLD.